Konstruksi Perlindungan Hukum Terhadap Anak Sebagai Korban Kekerasan Dalam Relasi Pacaran Yang Mengandung Ketimpangan Usia: Analisis Normatif - Naurah Afifah Nurwati; Putri Maharani; Asep Suherman (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
This study outlines the urgency of legal protection for children who are victims of violence in the context of romantic relationships with significant age differences. In such relationship dynamics, the age difference is not merely a statistical figure, but a determinant factor that creates unequal power relations. The chronologically more mature party generally has dominance in emotional, economic, and life experience aspects, which is then used as an instrument to control, dominate, and even manipulate the child who is still psychologically developing. Furthermore, this striking age difference fundamentally invalidates the validity of the child's consent. Legally and psychologically, the consent given by children in unequal relationships is often false, born of invisible psychological pressure, a sense of dependency, or the child's inability to identify forms of exploitation. This leaves children in a highly vulnerable position to a wide spectrum of violence, ranging from physical violence and psychological trauma to sexual exploitation, often disguised as a romantic relationship.